Association between body mass index and medication-overuse headache among individuals with migraine: a cross-sectional study - Huanxian Liu; Hongru Zhao; Kaiming Liu; Zhihua Jia; Ming Dong; Yingying Cheng; Yudan Lv; Kang Qu; Wei Gui; Jianjun Chen; Dan Zhang; Zhiliang Fan; et al. (Obesity Facts, 2024)
Introduction: Medication-overuse headache (MOH) is a secondary chronic headache disorder that occurs in individuals with a pre-existing primary headache disorder, particularly migraine disorder. Obesity is often combined with chronic daily headaches and is considered a risk factor for the transformation of episodic headaches into chronic headaches. However, the association between obesity and MOH among individuals with migraine has rarely been studied. The present study explored the association between body mass index (BMI) and MOH in people living with migraine. Methods: This cross-sectional study is a secondary analysis of data from the Survey of Fibromyalgia Comorbidity with Headache study. Migraine and MOH were diagnosed using the criteria of the International Classification of Headache Disorders, 3rd edition. BMI (kg/m2) is calculated by dividing the weight (kg) by the square of the height (m). Multivariable logistic regression analysis was used to evaluate the association between BMI and MOH. Results: A total of 2,251 individuals with migraine were included, of whom 8.7% (195/2,251) had a concomitant MOH. Multivariable logistic regression analysis, adjusted for age, sex, education level, headache duration, pain intensity, headache family history, chronic migraine, depression, anxiety, insomnia, and fibromyalgia, demonstrated there was an association between BMI (odds ratio [OR], 1.05; 95% confidence interval [CI], 1.01–1.11; P = 0.031) and MOH. The results remained when the BMI was transformed into a category. Compared to individuals with Q2 (18.5 kg/m2 ≤ BMI ≤ 23.9 kg/m2), those with Q4 (BMI ≥ 28 kg/m2) had an adjusted OR for MOH of 1.81 (95% CI, 1.04-3.17; P = 0.037). In the subgroup analyses, BMI was associated with MOH among aged more than 50 years (OR, 1.13; 95%, 1.03-1.24), less than high school (OR, 1.08; 95%, 1.01-1.15), without depression (OR, 1.06; 95%, 1.01-1.12), and without anxiety (OR, 1.06; 95%, 1.01-1.12). An association between BMI and MOH was found in a sensitivity analysis that BMI was classified into four categories according to the World Health Organization guidelines. Conclusion: In this cross-sectional study, BMI was associated with MOH in Chinese individuals with migraine.